Komunikasi Persuasi terhadap Upaya Pencegahan Kecanduan Permainan Judi Online di Kalangan Mahasiswa: Studi Kasus pada Mahasiswa Pemain Judi Online di Kota Surakarta - Zhafira Nazwa Kharismalihah; Andika Sanjaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was written because some students have been negatively affected by online gambling, and to figure out how to stop it. Online gambling itself is a game that uses the internet and involves money or valuable items, where players top up their digital wallets or e-wallets to participate. Players can win or lose, and the game involves betting. The research question in this study is: How does persuasive communication influence students to engage in online gambling, and how can persuasive communication be used to prevent online gambling among students? The objective of this study is to understand how persuasive communication influences the mindset and behavior of students in Surakarta and to identify efforts or methods to prevent online gambling addiction. The benefits of this study are to obtain in-depth information regarding how persuasive communication patterns influence students in Surakarta and the preventive measures for online gambling. The theory used in this study is the learning theory or social cognitive theory. This study is classified as qualitative descriptive, with data collection through semi-structured interviews using snowball sampling.